Thucydides on Grand Strategy: Periclean Grand Strategy during the Peloponnesian War - Platias, Athanassios (Études helléniques / Hellenic Studies, 1998)
The purpose of this essay is to present Thucydides’ contribution to the study of strategy. It is in Thucydides’ text that we find for the first time in history an outline of a complete theory of grand strategy. As a case study, the essay examines the grand strategy that Athens, under Pericles’ direction, employed during the first phase of the Peloponnesian War. The Periclean grand strategy was a typical strategy of exhaustion, whose aim was to dissuade the enemy (Sparta) from continuing his attempt to overthrow the existing status quo. The essay argues that the Periclean grand strategy was an excellent strategic design, which ensured Athenian success in the struggle. Athens was defeated only when it abandoned this grand strategy; in fact, the departure from the Periclean grand strategy was the very reason for the Athenian defeat. Furthermore, this essay claims that the Periclean strategy of exhaustion contained the seeds of a) “the British way of warfare”, and b) the American Grand Strategy during the Cold War. Last, it argues that in the coming decades the employment of the strategy of exhaustion is bound to become more popular.